2004
DOI: 10.1104/pp.104.045674
|View full text |Cite
|
Sign up to set email alerts
|

Processes Modulating Calcium Distribution in Citrus Leaves. An Investigation Using X-Ray Microanalysis with Strontium as a Tracer

Abstract: Citrus leaves accumulate large amounts of calcium that must be compartmented effectively to prevent stomatal closure by extracellular Ca 21 and interference with Ca 21 -based cell signaling pathways. Using x-ray microanalysis, the distribution of calcium between vacuoles in different cell types of leaves of rough lemon (Citrus jambhiri Lush.) was investigated. Calcium was accumulated principally in palisade, spongy mesophyll, and crystal-containing idioblast cells. It was low in epidermal and bundle sheath ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 42 publications
6
44
0
Order By: Relevance
“…p-b, peak over background ratio as defined by Storey and Leigh (2004). n = 4 cells per leaf 8, four separate plants (mean + SE).…”
Section: Ca Is Preferentially Stored Within Mesophyll Cell Vacuoles Omentioning
confidence: 99%
See 1 more Smart Citation
“…p-b, peak over background ratio as defined by Storey and Leigh (2004). n = 4 cells per leaf 8, four separate plants (mean + SE).…”
Section: Ca Is Preferentially Stored Within Mesophyll Cell Vacuoles Omentioning
confidence: 99%
“…While at the other, low vacuolar Ca concentration ([Ca] vac ) may result from reduced exposure to apoplastic Ca 2+ . Studies of rough lemon (Citrus jambhiri) in which all leaf cells were exposed to strontium ions (as a tracer for Ca 2+ ) or high apoplastic [Ca 2+ ] ([Ca 2+ ] apo ) demonstrated that only certain cells had the ability to accumulate significant [Ca] vac (Storey and Leigh, 2004). This suggests transport capabilities of different cell types determine the ability to store Ca 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…Strontium is a non-nutrient trace element that is ingested and metabolised into mammalian tissues principally from food and drink. (Bowen 1979, Storey andLeigh 2004) enabling strontium to be successfully used as a…”
Section: Strontium Metabolism Into Bonementioning
confidence: 99%
“…1,2 Furthermore, the cellular location of a particular element is robust within an individual plant, but the cell-type that accumulates each element can vary between species. [1][2][3] Until recently, the mechanisms and physiological role for element compartmentation in different cell-types was unknown. In two papers published in 2011, single-cell analysis and sampling…”
Section: Introductionmentioning
confidence: 99%